International norms in regulating e-commerce: the electronic commerce chapter of the comprehensive Trans-pacific Partnership Agreement - Abdul Ghani Azmi, Ida Madieha; Phuoc, Jeong Chun (Universiti Malaysia Sarawak, 2020)
The Malaysian government has introduced a number of flagship initiatives to leverage on digital economy and tap the economic trade benefits it promises to the country. For digital economy to grow to its utmost potentials, a supportive eco-legal system is warranted, both at domestic level and international level. As at the heart of digital economy is speedy access to Internet as well as latest gadgets, applications and data analytics, facilitating transfer of data from one country to another should be a matter of first priority. Whilst government seeks to achieve that domestically by introducing relevant laws and regulations, it is no surprise that international norms on data transfer is equally imperative. Using doctrinal analysis, this article explores the provisions of the E-Commerce Chapter of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and compares them with existing domestic legal obligations. The E-Commerce chapter that contains provisions on spam, online personal data, location of computing facilities, among others, are in some ways requiring enhancement of existing legal obligation. The paper concludes that implementing CPTPP would not require much structural changes to the existing suite of e-commerce related legislation in Malaysia.